ACCESSIBILITY ANALYSIS OF STREET NETWORKS USING SPACE SYNTAX - Ozturk, Ozge; Gulgen, Fatih; Bilgi, Serdar; Kilic, Batuhan (BULGARIAN CARTOGRAPHIC ASSOC, 2018)
Accessibility is mainly based on street networks, which directs the pedestrian movement. Space syntax is one of the most used methods that explain how spatial form of a place affects pedestrian movement. The aim of this study is to examine the accessibility of the Davutpasa Campus for the pedestrians at Yildiz Technical University. Especially in the campus, walking is one the most important transport modes. In this study, the accessibility of campus has been analyzed by using Space syntax and GIS methods. At first, an axial map which represents open spaces of the campus has been generated from Open Street Map. Then, the axial and segment analysis is performed in depthmapX software with the remote link from QGIS. Some geometric and topological measures have been calculated by Space Syntax Toolkit through depthmapX. Finally, the results of this study have been discussed in the terms of spatial cognition and morphological properties of the campus. They also show accessibility of the campus network and provide a new approach for the campus plan.
Keywords: Space Syntax; Spatial analysis; Street network; Axial map; Walkability; Geography